Analisis Kebijakan Pengembangan Komoditas Kelapa Sawit Dan Dampaknya Terhadap Ekonomi Petani Di Lampung - Abdurohman muzaki; Erlin Kurniati (SUAN PUBLISHER, 2024)
This study aims to analyze oil palm commodity development policies in Lampung Province and their impact on farmers' economy. Palm oil is one of the leading commodities that has an important role in the regional economy, especially for farmers who depend on this agricultural sector. Policies implemented by the government, both at the regional and national levels, play a significant role in determining the direction of the development of the palm oil industry, including in terms of farmer empowerment, natural resource management, and environmental sustainability. The method used in this research is a qualitative approach with descriptive analysis. Data collection was conducted through in-depth interviews with oil palm farmers, local government officials, and agricultural experts, as well as document analysis related to existing policies. The results show that although the oil palm development policy in Lampung has contributed positively to increasing farmers' income, there are several challenges related to fluctuating commodity prices, lack of access to modern agricultural technology, and environmental sustainability issues that still need serious attention. The economic impact on oil palm smallholders is highly dependent on the stability of policies that support the sector, as well as the strengthening of distribution systems and training to increase the capacity of farmers. Therefore, a more integrative policy is needed that not only focuses on increasing production, but also on better social and environmental welfare for oil palm farmers in Lampung.